FAKTOR DEMOGRAFI YANG BERHUBUNGAN DENGAN PERILAKU BULLYING DI KALANGAN MAHASISWA KEPERAWATAN - Rakinaung, Natalia; Geneo, Martinus; Budiawan, Helly (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Introduction: Bullying behavior among nursing students can affect the mental health of students and also the quality of health care in nurses' clinical practice. Objective: The aim of this research is to find out the relationship between demographic factors and bullying behavior of nursing students. Methods: This study is a correlation analytical study using cross sectional design with a sample of 62 nursing students using purposive sampling techniques. Research instrument using the Olweus Bully-Victim Questionnaire (OBVQ-R). Data analyzed with Spearman's rho test through the SPSS 26.0 application. Results: Research shows that there is a significant relationship between bullying victims with age and gender, and there is no significant link between the victim and the bullyer with the academic time span and family income. Conclusions: Educational institutions need to implement bullying behavior prevention programmes and provide counselling to prevent the spread of bullyed behaviour among nursing students in order to promote the mental health of students and the quality of student service in the practice of nurse services.